Analisis Kontribusi Pajak Daerah terhadap Peningkatan Pendapatan Asli Daerah Provinsi Jawa Timur 2020 – 2024 - Anggun Prasiwi; Gladys Lhexya Faradhila; Mila Zulficka Dewi; Adinda Zakiya Putri Rahmandhani (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study discusses the role of Motor Vehicle Tax (PKB) and Motor Vehicle Transfer Tax (BBNKB) in supporting the increase in Regional Original Revenue (PAD) of East Java Province for the period 2020 to 2024. This study uses a descriptive quantitative approach. The data used are secondary data obtained from the government. The study results indicate that PKB consistently contributes significantly to PAD, with an average of 43.78%, which falls into the category of highly contributing. Meanwhile, BBNKB shows a fairly stable contribution of 22.74%, categorized as moderately contributing. Both types of taxes serve as the backbone of local revenue, particularly in the context of fiscal autonomy and strengthening local development capacity. This study recommends the need to optimize local tax strategies, including improving service delivery and taxpayer compliance, to ensure that PAD revenue continues to grow sustainably.